An early embryonic product of the gene shaggy encodes a serine/threonine protein kinase related to the CDC28/cdc2+ subfamily. - Bourouis, M.; Moore, P.; Ruel, L.; Grau, Y.; Heitzler, P.; Simpson, P. (The EMBO Journal, 1990)
The product(s) of the gene shaggy (sgg) is required for seemingly unrelated events during the development of Drosophila melanogaster. In embryos, maternal and zygotically derived sgg products are required initially to construct a normal syncytial blastoderm and later for normal segmentation. Furthermore, in mutant animals a process of intercellular communication that is required for the segregation of the neural and epidermal lineage during the formation of the central nervous system and the adult peripheral nervous system is disrupted. Here we describe a transcription unit of approximately 40 kb lying within the cloned chromosomal interval 3B1, and provide evidence that it encodes the sgg+ function. Of seven developmentally regulated transcripts that are partially generated by alternative splicing, two seem to be responsible for early sgg activity. Sequence analysis of corresponding cDNA(s) predicts a protein of 514 amino acids with a canonical catalytic domain found in serine/threonine specific protein kinases, linked to an unusual region rich in Gly, Ala and Ser. A search for homologies as well as a comparative study of the kinase catalytic domain with that of other proteins, revealed that the protein kinase domain of sgg is distantly related to the members of the CDC28/cdc2+ subfamily of protein kinases, all of which play cardinal roles in the regulation of the yeast and mammalian cell cycles. Ubiquitous expression of sgg transcripts was found during embryonic stages. A possible role of the sgg protein in a signal transduction pathway necessary for intercellular communication at different stages of development is discussed.